Penerapan Metode Brainstorming Pada Mata Pelajaran Fiqih Di MTs Ar-Ridha Medan - Mutia, Meuthia Putri; Setiawan, Hasrian Rudi (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research aims to determine the application of the Brainstorming learning method at MTs Ar-Ridha in Fiqh subjects with a focus on improving the ability to express opinions. This research is qualitative research that is descriptive in nature and is included in the type of field research or field research. The data analysis technique used is based on the Miles and Huberman approach which includes data collection, data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, triangulation techniques were used. The research results show that the application of the Brainstorming method to Fiqh subjects involves a series of stages, such as: 1) planning, 2) implementation, and 3) evaluation.